Women as Environmental Cadres: Case Study in Activities of “Fostering Family Welfare”or PKK in Malang 2018 - Irza Khurun'in; Tia Subekti (Journal of Politics and Policy, 2020)
Ecofeminism is present to bridge the study between ecology and feminism. He tried to connect the relationship between natural damage and the dominance of masculinity. Shiva and Mies strongly depicted women as natural caretakers of the environment in which it perpetuates traditional views on the gendered division of labor. This paper critically examines the ways in which women interpret their roles and relationships related to nature by using specific case study of women environmental cadres through PKK (Fostering Family Welfare) in Malang. This article argues that the women involvement in environmental conservation through PKK is not their acknowledgement of their distinct relationship to their natural environment. Instead, it was the product of hegemony of knowledge and power by government and environmental activists. It shows that ecofeminism ignores political aspects in which actually puts the burden of environmental damage on women with portraying women as